Use of Complementary Therapy in Juvenile Idiopathic Arthritis: An Advanced Study Approach - Szigethi, Muschi; Mena, Andrea; Norambuena, Ximena; Jiusan, Lorena; Quezada, Arnoldo (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
Complementary and alternative medicine (CAM) has been defined as a group of diverse medical and health care systems, practices, and products not considered in conventional medicine. Efficacy and safety of many of CAM therapies for Juvenile Idiopathic Arthritis (JIA) have not been clearly demonstrated. The objective of this study was to assess the effectiveness and safety of Bach flowers remedies as a CAM therapy in children with Juvenile Idiopathic Arthritis. Methods: Prospective, randomized, double-blind, placebo-controlled trial in 30 patients with JIA assigned to receive Bach flowers therapy (Healing HerbsÒ, United Kingdom) or placebo. Both groups underwent five medical visits over the course of 5 months follow up. At first and last visit, the American College of Rheumatology Pediatric 30 (ACR Pedi-30) criteria for improvement were applied. At all medical visit, clinical evaluation, symptoms, adverse events, changes in conventional medication and parents and patient’s perception of the therapy were evaluated. Results: We found that 67% (10/15) of patients in the flower solution group and 77% (10/13) in the placebo group improved according to ACR-30 score, difference was not statistically significant (p=0.83). Ten children had no changes in drug regimen, 5 were of the flower therapy group (p>0.05). Nine children were able to decrease their use of medications; 6/9 in the flower therapy group, difference was not significant (p=0.43). About of opinion of the complementary therapy received, 75% (21/28) patients or family members rated the therapy as good or very good, 14 from the flower therapy group and 8 from the placebo group with no significant differences between groups (p= 0.19). Conclusions: Bach flower therapy in JIA was not able to demonstrate greater effectiveness than a placebo in this study. Conventional therapy for JIA should not be replaced by CAM therapy, however, this study shows this type of therapy to be safe and therefore it may be used as a complement to traditional therapy. Bach flower therapy can help and support patients and families with emotional disturbances. Pediatricians could have an open relationship with families on this topic, allowing for discussion, information sharing, and research on chronic diseases.